2012
DOI: 10.1088/0256-307x/29/9/092301
|View full text |Cite
|
Sign up to set email alerts
|

Near-Yrast Structures in Odd-Odd 122 I Nucleus

Abstract: Excited states of the odd-odd nucleus 122 I are investigated via the fusion-evaporation reaction 116 Cd( 11 B,5n) at a beam energy of 68 MeV. The two most strongly populated bands in 122 I are observed up to excitation energies around 10.5 MeV. Their possible configurations at lower spins are assigned to πœ‹β„Ž 11/2 βŠ— πœˆβ„Ž 11/2 and πœ‹β„Ž 11/2 βŠ— πœˆπ‘‘ 5/2 based on the observed population, B(M1)/B(E2) values, alignments and signature splitting. E1 transitions are observed connecting the πœ‹β„Ž 11/2 βŠ— πœˆπ‘‘ 5/2 band to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
4
4
0
Order By: Relevance
“…Some partial results from the current experiment were reported earlier [9][10][11]. After our reports, a similar experimental result for this nucleus was presented by another group [12,13].…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Some partial results from the current experiment were reported earlier [9][10][11]. After our reports, a similar experimental result for this nucleus was presented by another group [12,13].…”
Section: Introductionsupporting
confidence: 91%
“…4, were assigned to be negative parity based on a 9 βˆ’ band head. Our result was confirmed by a later work [12,13]. Furthermore, the low-lying structures on which collective states are based were not defined until our work.…”
Section: Ξ³ Timesupporting
confidence: 78%
See 1 more Smart Citation
“…[8,9] However, the later study by Moon et al [11,12] assigned it to the πœ‹β„Ž 11/2 βŠ— πœˆβ„Ž 11/2 configuration. Similar controversial assignment also exists in other odd-odd iodine nuclei [11] including 122 I, for which our conclusion [7] agrees with that of Moon et al Likewise, for the present case of 120 I, the πœ‹β„Ž 11/2 βŠ— πœˆβ„Ž 11/2 configuration assignment is again considered to be reasonable. Band I1 was reported by Kaur et al [8,9] up to the state de-excited by the 506 keV transition shown in Fig.…”
supporting
confidence: 93%
“…Angular correlations of the 𝛾rays were then evaluated by using the ADO methodology as used in Ref. [7].…”
mentioning
confidence: 99%